Early life adverse experiences and loneliness among young adults: The mediating role of social processes - Landry, Jyllenna; Asokumar, Ajani; Crump, Carly; Anisman, Hymie; Matheson, Kimberly (Frontiers in Psychology, 2022)
Loneliness has been described as endemic among young people. Such feelings of social isolation ‘even in a crowd’ are likely linked to adverse early life experiences that serve to diminish perceptions of social support and intensify negative social interactions. It was suggested in the present series of survey studies that childhood abuse, which compromises a child’s sense of safety in relationships, may affect social processes that contribute to loneliness in young adulthood. Study 1 assessed different adverse childhood and adult experiences in relation to loneliness among young adults (N=171). Linear regression analyses indicated that childhood abuse was uniquely associated with greater loneliness, and this relationship was partially mediated by the perceived availability of social support. Study 2 (N=289) assessed different forms of childhood abuse and demonstrated that early life emotional abuse was a unique predictor of loneliness, and this relationship was fully mediated by lower perceived support or value in social connections (social connectedness) and more frequent unsupportive interactions with friends. Study 3 evaluated the implications of the age of occurrence of abuse (N=566). Both emotional and sexual abuse predicted young adult loneliness regardless of age; abuse that was recalled to have occurred at very early ages (0 to 5 years) was not predictive of loneliness over and above consideration of events that happened in older childhood. These relationships were at least partially mediated by perceived social support, social connectedness, and in the case of emotional abuse, unsupportive interactions with friends. Our results add to mounting evidence pointing to the prevalence of loneliness among young adults and the links to adverse early life experiences that may serve to shape appraisals of safety, value, and personal worth in social relationships.